Model Affitin and PEG modifications onto siRNA lipid nanocapsules: cell uptake and in vivo biodistribution improvements. Issue 47 (30th August 2019) - Resnier, Pauline; Lepeltier, Elise; Emina, Anthea Lucrezia; Galopin, Natacha; Bejaud, Jérôme; David, Stephanie; Ballet, Caroline; Benvegnu, Thierry; Pecorari, Frédéric; Chourpa, Igor; Benoit, Jean-Pierre; Passirani, Catherine
Abstract : Surface modifications of siRNA LNCs were assessed with innovative TE-PEG polymers and an Affitin model, in comparison to classic DSPE-PEG LNCs, in order to evaluate the potential tumor targeting of siRNA after intravenous administration. Abstract : Malignant melanoma is an aggressive tumor, associated with the presence of local and/or distant metastases. The development of gene therapy by the use of small interfering RNA (siRNA) represents a promising new treatment. However, the protection of this biomolecule is necessary in order for it to be intravenously administrated, for example via its incorporation into nanomedicines. In parallel to the passive targeting usually obtained by pegylation, various studies have aimed at developing "smart" nanomedicines to efficiently deliver the drug to tumor sites. In this work, siRNA loaded lipid nanocapsules (LNCs) were modified with DSPE-polyethylene glycol (DSPE-PEG), tetraether-PEG (TE-PEG) and/or with an Affitin model, to assay multiple targeting strategies. The uptake of fluorescently labelled LNCs, nanocarrier integrity and siRNA release into human SK-Mel28 melanoma cells were studied by flow cytometry, conventional confocal microscopy and by confocal spectral imaging in a Förster Resonance Energy Transfer (FRET) mode. Surface modified siRNA LNCs were followed after human plasma incubation and after intravenous injection, in order to compare the stealth properties. Finally, the biodistribution of the different siRNA LNCs in healthy and melanoma tumor bearing mice models was assessed by in vivo biofluorescence imaging (BFI), to evaluate the potential tumor targeting ability. The post-insertion of DSPE-PEG induced a strong decrease of the internalization into melanoma cells compared to TE-PEG modification. Both PEG polymer decorations induced a great plasma protection of siRNA but only DSPE-PEG led to stealth properties, even at low concentration (5 mM). The Affitin grafting by thiolation of DSPE-PEG was validated on siRNA LNCs. DSPE-PEG-Affitin LNCs were not detected in this melanoma tumor model but did not show unspecific accumulation in organs. DSPE-PEG and TE-PEG LNCs induced a significant intratumoral accumulation of modified LNCs.